2006
DOI: 10.1126/science.1128057
|View full text |Cite
|
Sign up to set email alerts
|

Structure of TonB in Complex with FhuA, E. coli Outer Membrane Receptor

Abstract: The cytoplasmic membrane protein TonB spans the periplasm of the Gram-negative bacterial cell envelope, contacts cognate outer membrane receptors, and facilitates siderophore transport. The outer membrane receptor FhuA from Escherichia coli mediates TonB-dependent import of ferrichrome. We report the 3.3 angstrom resolution crystal structure of the TonB carboxyl-terminal domain in complex with FhuA. TonB contacts stabilize FhuA's amino-terminal residues, including those of the consensus Ton box sequence that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
273
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(297 citation statements)
references
References 17 publications
15
273
2
1
Order By: Relevance
“…An independent test of this model came with the recent determination of the structure of the periplasmic domain of TonB in complex with two TonB-dependent receptors, FhuA (23) and BtuB (24). The coevolving signaling network bifurcates near the periplasmic surface of the transporter, with the first branch ending in the pocket containing the switch helix and the TonB-box and the second extending across the periplasmic surface of the plug to the opposite side of the barrel (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An independent test of this model came with the recent determination of the structure of the periplasmic domain of TonB in complex with two TonB-dependent receptors, FhuA (23) and BtuB (24). The coevolving signaling network bifurcates near the periplasmic surface of the transporter, with the first branch ending in the pocket containing the switch helix and the TonB-box and the second extending across the periplasmic surface of the plug to the opposite side of the barrel (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TonB is a three-domain protein containing an N-terminal transmembrane helix that anchors the protein in the cytoplasmic membrane, a central proline-rich domain that resides within the periplasm and a C-terminal globular domain that directly contacts outer membrane receptors. Two structures of the C-terminal domain of TonB complexed with an outer membrane receptor are now available (Pawelek et al 2006;Shultis et al 2006).…”
Section: Biological Contextmentioning
confidence: 99%
“…Over the past three decades, many aspects of this TonB-ExbB-ExbD-dependent transport system have been revealed. The crystal structures of several OM transporters and their complexes with TonB are now known (Ferguson et al, 1998(Ferguson et al, , 2002Buchanan et al, 1999;Ferguson and Deisenhofer, 2004;Pawelek et al, 2006;Shultis et al, 2006;Krieg et al, 2009), the signal transduction of OM transporters by interaction with TonB has been elucidated (Ferguson et al, 2007;Kim et al, 2007) and the rotational mechanism of TonB motion has been reported (Jordan et al, 2013). However, with regard to the substrates of the transport system, we are probably only seeing the 'tip of the iceberg' (Schauer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%